ANALISIS SEMIOTIKA ROLAND BARTHES MAKNA KURSI KOSONG TAYANGAN MATA NAJWA EDISI MENANTI TERAWAN - Rista Mala; Umi Rahmawati; Dian Novitasari (Jurnal Komunikasi dan Budaya, 2021)
The Coronavirus disease (Covid-19) pandemic has an impact on changes in Indonesia and even the world. The increasing number of patients who are positively exposed to the virus is making people " worry " will spread. However, regarding the handling of Covid-19, the role of the government, especially the minister of health, is in the spotlight where it rarely appears media provides an explanation of the information on the development of covid-19. Apart from the government, the media is one of the most important in providing information related to the Covid-19 pandemic. both of printing media and electronics media to new media covered and preach through television about handling covid-19. One of the media television who participates share in the handling of related covid-19 is the program Matanajwa. The research is aimed to analyze impressions MataNajwa interviewed seat vacant which contains a meaning by using the theory of semiotics of Roland Barthes of the order first is denotative and order connotative to find myths in order marker in the behind MataNajwa. Research is using approach qualitative to describe the meaning of which are on display MataNajwa edition of Menanti Terawan and the research is to use the type of paradigm critical. The results of this study can be found that the meaning of an empty chair in the broadcast is Terawan, who is considered to have not optimal performance and is considered often absent in the media in handling Covid-19. Myths are found in impressions is 1. Minister Terawan should resign from his post and 2. Seats empty present the Minister Terawan are considered not exist. In the broadcast, MataNajwa made the figure of Terawan as an object of protest against one of the government's performances in dealing with the pandemic. Keyword: Pandemic , Semiotics, Seat Empty